2016
DOI: 10.1016/j.gloenvcha.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable livelihoods in the global land rush? Archetypes of livelihood vulnerability and sustainability potentials

Abstract: Large-scale land acquisitions (LSLAs) have become a major concern for land use sustainability at a global scale. A considerable body of case studies has shown that the livelihood outcomes of LSLAs vary, but the understanding of factors and processes that generate these livelihood outcomes remains controversial and fragmented in terms of cases, contexts, and normative orientations. Therefore, this study presents a meta-analysis of case studies and applies the archetypes approach developed in global change resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(139 citation statements)
references
References 102 publications
4
118
0
4
Order By: Relevance
“…For instance, Burnod et al (2013) show how a Malagasy community was able to self-organize and protect its land rights by forming coalitions with a like-minded state department, which successfully competed with another LSLA-friendly state department. By contrast, this community-based strategy is unlikely to protect land rights, if community leaders or the strongest forces within government prioritize LSLA for development (Wolford et al 2013, Oberlack et al 2016. Seufert (2013) argues that the transnational Voluntary Guidelines of Responsible Governance of Tenure (VGGT) helped raise awareness and offer practical guidance to governments, companies, and civil society; but their effectiveness for tenure security depends on mechanisms within states to hold decision makers accountable to the VGGT standards.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Burnod et al (2013) show how a Malagasy community was able to self-organize and protect its land rights by forming coalitions with a like-minded state department, which successfully competed with another LSLA-friendly state department. By contrast, this community-based strategy is unlikely to protect land rights, if community leaders or the strongest forces within government prioritize LSLA for development (Wolford et al 2013, Oberlack et al 2016. Seufert (2013) argues that the transnational Voluntary Guidelines of Responsible Governance of Tenure (VGGT) helped raise awareness and offer practical guidance to governments, companies, and civil society; but their effectiveness for tenure security depends on mechanisms within states to hold decision makers accountable to the VGGT standards.…”
Section: Discussionmentioning
confidence: 99%
“…Although the headman originally denied wrongdoing, a document signing away the land with his signature on it eventually came to light, causing him to resign from his position in disgrace. 4 However, the damage had been done, and by the time the villagers realized what had happened, their farmland had been seized, cleared and planted with rubber seedlings, leaving the 92 families in the community with no agricultural or common lands. All they had left was the land where their houses are located.…”
Section: Yeup Village Thateng District Xekong Province Southern Laosmentioning
confidence: 99%
“…Indeed, a large number of case studies situated in various parts of the world, and especially in developing countries in the tropics, have demonstrated that these developments have often resulted in the displacement of small-scale farmers from their farmlands, the loss of common lands and forests important for rural livelihoods, the loss of biodiversity and a reduction in landscape diversity, and various other socio-environmental impacts on rural communities (Hall et al, 2011 [7]; White et al, 2012 [2]; Borras and Franco, 2012 [8]; McMichael, 2012 [9]; Hall et al, 2015 [10]; Gingembre, 2015 [11]), including in mainland Southeast Asia (Barney, 2009 [12]; Baird, 2011 [13]; Delang et al, 2012 [14]; Kenney-Lazar, 2012 [15]; Global Witness, 2013 [16]; Neef et al, 2013 [17]; McAllister, 2015 [18]; Schönweger and Messerli, 2015 [19]; Messerli et al, 2015 [20]). Oberlack et al (2016) [4], in a recent review article of a large number of case studies in various parts of the world associated with large-scale land acquisitions, have identified the enclosure of livelihood assets, elite capture, the selective marginalization of people already living in precarious circumstances, and the polarization of development narratives as key causes of adverse livelihood changes globally. Competitive exclusion of farmers, the failure large-scale land concessions for rubber in southern Laos are heavily influenced by the positionality 1 of the people involved, and associated "political memories", or memories of past wars and other conflicts.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial resilience of the smallholder scale is influenced by both the national scale and the global scale, and can thus reflect the change of the spatial resilience of the smallholder livelihood [99]. The spatial resilience at the national scale is influenced by the national system, which cannot separate between the local scale and the global scale.…”
Section: The Hierarchical Structure Of Spatial Resiliencementioning
confidence: 99%
“…The regulations of the spatial resilience about smallholder livelihoods are difficult to rely on at smallholder scale. Therefore, to achieve self-improvement, we need to use the existing mature smallholder livelihood security system to integrate cross-scale protection [99]. The spatial resilience of the urban-rural transformation mainly relies on the improvement of the self-learning ability of stakeholders on different scales of the system, while constantly improving the regulation of market factors in the GPS.…”
Section: Optimization Strategy Of Spatial Resiliencementioning
confidence: 99%